Effectiveness of genetic cascade screening for familial hypercholesterolaemia using a centrally co-ordinated clinical service: An Australian experience. Issue 1 (March 2015) - Bell, Damon A.; Pang, Jing; Burrows, Sally; Bates, Timothy R.; van Bockxmeer, Frank M.; Hooper, Amanda J.; O'Leary, Peter; Burnett, John R.; Watts, Gerald F.
Abstract: Background: Familial hypercholesterolaemia (FH) is a co-dominantly inherited disorder of low-density lipoprotein (LDL) catabolism, causing elevated LDL-cholesterol and premature coronary artery disease (CAD). Several guidelines recommend genetic cascade screening relatives of probands (index cases) with genetically proven FH, but experience in a clinical service setting is limited. Methods: Relatives from 100 index cases with genetically confirmed FH underwent genetic and lipid testing via a centralised screening program in Western Australia. The program's effectiveness was evaluated as the number of newly diagnosed relatives with FH per index case and the proportional reduction in LDL-cholesterol after treatment. Results: Of 366 relatives tested for FH, 188 (51.4%) were found to have a pathogenic mutation. On average, 2 cases were detected per index case. Affected relatives were younger and less likely to have physical stigmata of FH and premature CAD than index cases (p < 0.001). Of the new cases, 12.8% had hypertension, 2.7% had diabetes and 16.0% were smokers; 48.4% were already on statin therapy and these were older (p < 0.001) and had more vascular risk factors and CAD (p < 0.01) than those not on therapy. Significant reductions in LDL-cholesterol (−24.3%, p < 0.001) were achieved overall, with previously untreated new cases of FH attaining a maximal average reduction of 42.5% in LDL-cholesterol after drug therapy. Over 90% of subjects were satisfied with screening and care. Conclusion: Genetic cascade screening co-ordinated by a centralised service is an effective and acceptable strategy for detecting FH in an Australian setting. A significant proportion of new cases exhibit other CAD risk factors and are already on statins, but have not received a prior diagnosis of FH. Highlights: Centrally co-ordinated genetic and cholesterol cascade testing for FH is effective, feasible and acceptable. On average, two additional new cases are identified per index case. Many FH cases exhibit other CAD risk factors and are already on statins. Follow-up and therapy achieves significant reductions in plasma LDL-cholesterol.